Effect of Chrysanthemum Plants to Artificial Defoliation and Disbudding on Growth and Yield: _ - I Gusti Made Arjana; I Nyoman Rudianta; Ketut Agung Sudewa; A.A. Putri Risa Andriani (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
The market outlook for chrysanthemum flowers is extremely optimistic, as domestic and international consumer demand has increased over the past five years. The development of chrysanthemum plants is anticipated to positively affect the region's employment opportunities, economic growth, and service sector growth. Along with the increasing intensity of chrysanthemum cultivation in various regions, more in-depth research on chrysanthemum flowers is required to improve quality and added value and utilize the potential of locally available resources that are simple for farmers to apply and have a significant impact on improvement. The majority of chrysanthemum cultivation business actors are small farmers. Chrysanthemum plant technology is distinct from other horticultural crops, requiring special maintenance such as Disbudding, adding artificial light, artificial Defoliation, and the erection of plant enforcement nets. The research method employs the Factorial Group Random Design. The first factor is artificial Defoliation including no defoliation, Defoliation at 30 dap (day after planting) , and Defoliation at 60 dap. The second factor is disbudding including no disbudding, disbudding at 60 dap, and disbudding at 90 dap. The results demonstrated that the interaction between artificial Defoliation and disbudding significantly affected flower stalk weight but did not affect other variables. The treatment of leaf defoliation had significant to very significant effects on all observed variables, except for the weight of flower stalks, which was unaffected. At the same time, the disbudding treatment significantly affects all observed variables. The interaction between leaf defoliation at 30 dap and disbudding at 60 dap resulted in the heaviest average flower stalk weight of 93.58 grams. Artificial Defoliation at 30 dap increased the yield of economically viable fresh flower weight by 8.09 percent compared to when Defoliation was not performed. The 60 dap Disbudding treatment increased the yield of fresh flower weight by 9.25% when compared to the control.